PENGARUH WAKTU INKUBASI TERHADAP DIAMETER ZONA HAMBAT ANTIBIOTIK PADA UJI SENSITIVITAS BAKTERI KLEBSIELLA PNEUMONIA - Atik Martsiningsih; Suyana Suyana; Aisyiah Noviani; Ullya Rahmawati; Sujono Sujono; Fardhiasih Dwi Astuti (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background: Several analytical factors can affect the diameter of the inhibition zone; This factor must beinvestigated toguarantee thevalidityofthe sensitivitytestresults. Aims: This study was to determine the pattern of influence of variations in incubation time on thediameterofthe antibiotic inhibition zone in the sensitivity test of Klebsiella pneumoniae. Methode: this research is a pre experimental design with a Static Group Comparison design.The diameter of the antibiotic inhibition zone with variations in incubation time was measured and analyzeddescriptively.The results: The diameter of the inhibition zone on the variation of the incubation time showed a patternof the influence of the incubation time on the diameter of the antibiotic inhibition zone in the bacterialsensitivity test, namely at 6-18 hours, an increase in the diameter of the inhibition zone and 18-48 hours a decrease in the diameter of the zone. Inhibite ach antibiotic. Conclucion:This study concludes that the reisasignificant effect with the pattern of theinitial incubation time(6-18hours) affecting the broader or larger diameter of the inhibition zone and the subsequent incubation time of 18-48 hours decreasing the diameter of the inhibition.Keywords: Inhibition zone diameter, incubation time, sensitivity test